Kelimpahan Chlorella sp. dan Clamydomonas sp.: Kualitas Air, Pertumbuhan Dan Feed Convertion Ratio Udang Vaname (Litopenaeus vannamei) - Muhammad Akbarurrasyid; Achmad Sofian; Dinno Sudinno; Vani Ilasanti Maryani (Jurnal Perikanan Unram, 2024)
Chlorophyceae groups, such as Chlorella sp. and Chlamydomonas sp., are a stable group of phytoplankton with the highest abundance in Litopenaneus vannamei ponds. These two types can be used as determinant factors for water quality, growth, and Feed Conversion Ratio (FCR) in L. vannamei farming. This study aims to determine the correlation of Chlorella sp. and Chlamydomonas sp. on the water quality, growth, and FCR in L. vannamei farming. This study was conducted by survey and identification of plankton, water quality, growth, and FCR. The identified plankton was conducted using Principal Component Analysis (PCA) on water quality, growth, and FCR. The results of the study obtained a total abundance of Chlorella sp. and Chlamydomonas sp. of 91.93%. The water quality was found that most parameters comply with standards for L. vannamei farming activities, except for the parameters phosphate, nitrate, nitrite, Total Organic Matter (TOM), and ammonia. The abundance of Chlorella sp. and Chlamydomonas sp. has a strong correlation with a parameter of water quality in all ponds. The growth rate of Mean Body Weight in ponds is 0.4 – 24.43 grams/shrimp and has a strong correlation with the abundance of Chlorella sp. and Chlamydomonas sp. according to the significance value (p-value) of approximately 0.004 – 0.636. FCR value is 0.3-2.23 and has a strong correlation with the abundance of Chlorella sp. and Chlamydomonas sp. according to the eigenvalue of 1.032-1.670. The eigenvalue of the pond represents approximately 54.364% (pond 1), 55.658% (pond 2), 1.236, and 1.032 (pond 3) of the variable diversity. The results of the study showed that the abundance of Chlorella sp. and Chlamydomonas sp. is an indicator that influences the environment quality, growth, and Feed Conversion Ratio.